Juridical Study of Inheritance Rights of Children Out of Wedlock According to Marriage Law No. 1 of 1974 - Pitang, Govara Remeina; Pasyah, Rabbil Arya; Muzacky, Ahmad (CV. Rayyan Dwi Bharata, 2023)
This journal reviews marriage where at the present time there are more and more problems being experienced regarding marriage, especially young people who carry out emergency marriages or can also be called tambelan marriages. These emergency marriages produce many children who have been produced before the marriage is carried out, giving rise to a question regarding the status of children out of wedlock. Seeing the prevalence of this phenomenon, the authors conducted research normatively using sources from Law No. 1 of 1974 concerning marriage and also the Criminal Procedure Code/B.W. with the aim of digging up information and looking at legal perspectives to increase knowledge about what rights are obtained from both parents and also what is the status of children out of wedlock.